Neural Effects of Physical Activity and Movement Interventions in Individuals With Developmental Disabilities–A Systematic Review - Su, Wan-Chun; Amonkar, Nidhi; Cleffi, Corina; Srinivasan, Sudha; Bhat, Anjana (Frontiers in Psychiatry, 2022)
Individuals with developmental disabilities present with perceptuo-motor, social communication, and cognitive impairments that often relate to underlying atypical brain structure and functioning. Physical activity/movement interventions improve behavioral performance of individuals with and without developmental disabilities. Majority of the evidence on potential neural mechanisms explaining the impact of physical activity/movement interventions is based on studies in individuals with typical development; there is a dearth of systematic reviews synthesizing the neural effects of physical activity/movement intervention in individuals with developmental disabilities. In this systematic review, we have gathered evidence on the neural effects of physical activity/movement interventions from 32 papers reporting substantial neural effects and behavioral improvements in individuals with developmental disabilities. Chronic intervention effects (multiple sessions) were greater than acute intervention effects (single session). Specifically, using electroencephalogram, functional magnetic resonance imaging, diffusion tensor imaging, and functional near-infrared spectroscopy, studies found physical activity/movement intervention-related changes in neural activity, indicating normalization of cortical arousal in individuals with attention-deficit/hyperactivity disorder (ADHD), increased social brain connectivity in individuals with autism spectrum disorder (ASD), and more efficient executive functioning processes in individuals with a wide range of other developmental disabilities. Despite some of the promising results, more research with larger sample sizes, using standardized neuroimaging tools/variables, and research across multiple diagnoses are needed to further explore the neural mechanisms and increase the replicability of findings within and across diagnoses.